Prognostic Significance of C-reactive Protein-to-prealbumin Ratio in Patients with Esophageal Cancer - Matsunaga, Tomoyuki (Yonago Acta Med, 2019)
BACKGROUND: The prognostic value of combination of C-reactive protein and prealbumin (CRP/PAlb) in esophageal cancer remains unclear. METHODS: We enrolled 167 esophageal cancer patients who underwent curative esophagectomy. Univariate and multivariate analyses were performed to determine the prognostic signiﬁcance of various markers, including CRP-to-albumin (CRP/Alb) ratio, modified Glasgow prognostic score, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and prognostic nutritional index. RESULTS: Receiver operating characteristic analysis revealed the optimal cut-off value of each inflammatory factor, and CRP/PAlb ratio had the greatest discriminative power in predicting recurrence-free survival (RFS) among the examined measures (AUC 0.668). The 5-year overall survival and RFS rates were significantly lower in patients with high CRP/PAlb ratio than in those with low CRP/PAlb ratio (P < 0.001, P = 0.001, respectively). In the univariate analysis, RFS was significantly worse in patients with low BMI, T2 or deeper tumor invasion, positive lymph node metastasis, positive venous invasion, high CRP/PAlb ratio, high CRP/Alb ratio, high NLR, and high LMR. Multivariate analysis revealed that CRP/PAlb, but not CRP/Alb, was an independent prognostic factor along with lymph node metastasis. CONCLUSION: CRP/PAlb ratio was useful for predicting the prognosis of esophageal cancer patients.